2020
DOI: 10.1017/ice.2020.414
|View full text |Cite
|
Sign up to set email alerts
|

Management ofCandida aurisoutbreak in a tertiary-care setting in Saudi Arabia

Abstract: Objective: To describe local experience in managing an outbreak of Candida auris in a tertiary-care setting. Methods: In response to emerging Candida auris, an outbreak investigation was conducted at our hospital between March 2018 and June 2019. Once a patient was confirmed to have Candida auris, screening of exposed patients and healthcare workers (HCWs) was conducted. Postexposure screening included those who had had direct contact with or shared the same unit or ward with a laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 27 publications
0
24
1
Order By: Relevance
“…C. auris has previously been isolated with increasing frequency from Kuwait [ 14 , 45 ] and other Middle Eastern countries [ 22 ], and outbreaks have also been reported recently from two other (Oman and Saudi Arabia) nearby countries [ 21 , 40 , 41 ]. These reports together with our study and various outbreaks reported recently from other geographical locations [ 3 , 6 , 21 , 30 , 33 , 36 , 37 , 38 , 39 , 40 ] strongly support the emerging role of C. auris as a major cause of invasive infections and outbreaks in health care facilities worldwide that have been difficult to control. C. auris has presumably assumed this role due to several unique characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…C. auris has previously been isolated with increasing frequency from Kuwait [ 14 , 45 ] and other Middle Eastern countries [ 22 ], and outbreaks have also been reported recently from two other (Oman and Saudi Arabia) nearby countries [ 21 , 40 , 41 ]. These reports together with our study and various outbreaks reported recently from other geographical locations [ 3 , 6 , 21 , 30 , 33 , 36 , 37 , 38 , 39 , 40 ] strongly support the emerging role of C. auris as a major cause of invasive infections and outbreaks in health care facilities worldwide that have been difficult to control. C. auris has presumably assumed this role due to several unique characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Only 17 of 71 (24%) patients affected by the C. auris outbreak in our hospital developed candidemia. The data analyses from previous C. auris outbreaks have also shown that only a fraction (~14% to 40%) of affected patients develop candidemia [ 21 , 30 , 32 , 36 , 40 ]. The risk factors for invasive C. auris infections are similar to those for other Candida spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that once C. auris is introduced into a healthcare facility, it spreads rapidly among susceptible patients [40,41]. Thus far, C. auris outbreaks have been reported from the United States of America [42][43][44][45], Canada [46], Mexico [47], the United Kingdom [48,49], Spain [50,51], India [40,52], Pakistan [53], Russia [54], Saudi Arabia [55], Oman [56,57], Kuwait [58], Kenya [59], South Africa [60], and Colombia [61]. Studies describing single/multiple invasive infections and outbreaks in different countries or geographical locations in the last several years have been extensively reviewed, only some of which are cited here [29][30][31][32]38].…”
Section: Epidemiology Of C Auris Infectionsmentioning
confidence: 99%